P-Functionalized tetrathiafulvalenes from 1, 3-dithiole-2-thiones?. (1st October 2020) - Gese, A.; Akter, M.; Schnakenburg, G.; García Alcaraz, A.; Espinosa Ferao, A.; Streubel, R.
Abstract : Synthesis of mono- and bisphosphanylated 1, 3-dithiole-2-thiones is presented, including phosphite-mediated reductive C, C coupling reactions. Computational studies point to a spirothiaphosphirane and a S-heterocyclic carbene as key intermediates. Abstract : A protocol for the synthesis of mono- and bis-phosphanylated 1, 3-dithiole-2-thiones 2 and 3 is presented. The reaction of 2 or 3 with hydrogen peroxide–urea or elemental sulfur led to the corresponding P(v ) chalcogenide 1, 3-dithiole-2-thiones 4–7 . All compounds were characterized by 31 P, 1 H and 13 C NMR and IR spectroscopy and elemental analyses. Additionally, compounds 3 and 4 were analysed by single-crystal X-ray diffraction analysis. The reaction of 3 with P(OEt)3 led selectively to the tetrakis-phosphanylated tetrathiafulvalene derivative II via a reductive C 2, C 2 coupling reaction. A thorough computational analysis for the mechanism of phosphite-mediated reductive dimerization of 1, 3-dithiole-2-thiones was performed.